Pengaruh Profitabilitas, Resiko Bisnis Dan Pertumbuhan Penjualan Terhadap Struktur Modal pada Perusahaan Property dan Real Estate di BEI Periode 2016 - 2020 - Areza Marta Brona; Risal Rinofah; Pristin Prima Sari (MES Bogor, 2023)
Capital structure is a comparison between foreign capital and own capital. In principle, the company needs funding both from outside which is debt and from within which is joint capital, therefore the company must determine and compile how much capital the company must need. This study aims to analyze the effect of profitability, business risk and sales growth on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange for the period 2016-2020 partially and simultaneously. This study uses quantitative data types obtained from secondary data with sample data collection techniques through purposive sampling method. This research method uses descriptive method with data analysis tool using multiple linear regression method. The results of this study indicate that profitability as proxied by ROE has an insignificant negative effect on capital structure, business risk has a significant negative effect on capital structure and sales growth has an insignificant negative effect on capital structure. Meanwhile, simultaneously (together) profitability, business risk and sales growth affect the capital structure of property and real estate companies listed on the Indonesia Stock Exchange for the period 2016-2020. Keywords: Profitability, Business Risk, Sales Growth, Capital Structure.